What happens when registered nurses are caring for patients with tracheostomies in the ward of a referral hospital in Botswana? - Gontekanye Keagaetsho; Charlené Downing (Elsevier, 2021)
Background: Tracheostomy is the opening where the tracheostomy tube is inserted to create an artificial airway when a patient requires respiratory support. Nurses caring for patients with tracheostomies are expected to be familiar with current guidelines on routine care and the emergency management of complications. The researcher has observed that when arrangements are being made to transfer patients with tracheostomies from the intensive care unit to the ward, the registered nurse in the ward often try to delay the transfer, frequently refuse to care for patients, or try to avoid any activities around patients. Objectives: To explore and describe the lived experiences of registered nurses regarding their caring for patients with tracheostomies. Methods and sampling techniques: A qualitative, exploratory, descriptive and contextual research design, using a descriptive phenomenological approach, was implemented. A purposive sample of ten participants who volunteered and participated signed the informed consent. Individual, in-depth interviews were conducted and analysed using Giorgi's five-step method for descriptive data analysis. Results: The central theme revealed caring as empowering although challenging in an enabling therapeutic milieu. Caring, as a nurse's duty, featured prominently. Two main themes emerged. Caring in an enabling therapeutic milieu experienced as caring for the whole person, caring for patients as their professional duty and empowerment in their nursing care. Caring in a disenabling therapeutic milieu experienced as caring for patients as a clinical challenge, incompetent to care for patients effectively related to inadequate knowledge and skills, inadequate equipment and human resources and caring in a non-conducive therapeutic environment.